Youssef’s Syndrome following Cesarean Section - Ozer Birge; Ertugrul Gazi Ozbey; Mustafa Melih Erkan; Deniz Arslan; Ilkan Kayar (Case Reports in Obstetrics and Gynecology)
Youssef’s syndrome is characterized by cyclic hematuria (menouria), absence of vaginal bleeding (amenorrhea), and urinary incontinence due to vesicouterine fistula (VUF), the least common of the urogynecological fistulas. Youssef’s syndrome has a variable clinical presentation. A vesicouterine fistula is an abnormal pathway between the bladder and the uterus. The most common cause is lower segment Cesarean section. Conservative treatment may be appropriate in some cases, but surgery is the definitive treatment. Vesicouterine fistula should be suspected in cases presenting with urinary incontinence even years after Cesarean section. Diagnostic tests as well as necessary appropriate surgery should be performed on cases with suspected vesicouterine fistula. We present a 40-year-old multiparous woman with vesicouterine fistula after primary Cesarean section; she presented with urinary incontinence, hematuria, and amenorrhea 1 year after the birth. Here, we discuss our case with the help of previously published studies found in the literature.